Representation of Science Concepts in Local Folklore as a Source of Learning IPAS in Madrasah Ibtidaiyah - Alfiatur Rohmaniyah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The purpose of this study is to see how local folktales and science concepts can be used as learning resources in Natural and Social Science lessons in Madrasah Ibtidaiyah (MI). In this study, qualitative methods and content analysis techniques were applied to relevant local folktales. The main data sources were folktales from various regions in Indonesia, which were selected based on their relevance to science concepts in the IPAS curriculum. Data collection was conducted through document analysis of folktales, interviews with IPAS teachers, and observations on how folktales are applied in classroom learning. Using a descriptive approach, the data collected was analyzed to find and categorize the science concepts contained in the folktales. In addition, it was assessed the possibility of folklore can be used as learning media. The results showed that local folktales have great potential as a source of IPAS education covering physics and chemistry concepts, as well as natural phenomena and animal and plant life. Students can gain a better understanding of science concepts through folktales, which are more contextualized and easy to understand. Thus, folktales can be incorporated into IPAS learning to improve students' understanding, enrich their learning experience, and raise awareness of the importance of environmental conservation. In addition, this study suggests the creation of folklore-based learning modules and teacher training programs to maximize this potential.